Astragalus polysaccharides, chitosan and poly(I:C) obviously enhance inactivated Edwardsiella ictaluri vaccine potency in yellow catfish Pelteobagrus fulvidraco. Issue 87 (April 2019) - Zhu, Wentao; Zhang, Yanqi; Zhang, Jiacheng; Yuan, Gailing; Liu, Xiaoling; Ai, Taoshan; Su, Jianguo
Abstract: The yellow catfish ( Pelteobagrus fulvidraco ) is an economically important fish in China, but Edwardsiella ictaluri, an intracellular pathogenic bacterium, causes great losses to the culture industry. Currently, vaccination is the most promising strategy to combat the infectious diseases, while adjuvant can provide effective assistant for vaccines to enhance immune responses. In the present study, inactivated E. ictaluri vaccine was prepared, then Astragalus polysaccharides (APS), chitosan and poly(I:C) were employed as adjuvants to evaluate the effect on boosting immune responses and protecting yellow catfish against E. ictaluri . The survival rate was obviously improved after vaccination with APS, chitosan or poly(I:C) respectively, in addition, these three adjuvants could clearly protect the target tissue (intestine) by pathological sections in infectious experiments. In sera, total protein levels increased throughout the immunization stages, total superoxide dismutase levels continued to raise after vaccination, and lysozyme activity levels improved at different periods, examining by the commercial kits. Moreover, checking by real time quantitative RT-PCR assays, in both spleen and head kidney tissues which were the major immune organs, mRNA expressions of inflammatory cytokine IL-1β increased in the early stage of immunity, typical Th1 immune response cytokines IL-2 and IFN-γ2 rose up in the whole immune period, and IgM significantly enhanced in the adjuvant supplementation groups. The results demonstrated the good efficiency of APS, chitosan or poly(I:C) as adjuvant, and provided more options for the fish adjuvants. Highlights: APS, chitosan or poly(I:C) as adjuvant improves the survival rate of yellow catfish against E. ictaluri. These three adjuvants protect the intestine tissue which is the target tissue of E. ictaluri. These three adjuvants increase serum biochemical activities to resist bacteria. These three adjuvants reinforce inflammatory response, Th1 type immune response and IgM expression.